Beyond coding and counting: Exploring teachers' practical knowledge online through epistemic network analysis. (January 2023) - Sun, Zhong; Xu, Rumeng; Deng, Luyao; Jin, Fangzhou; Song, Zicong; Lin, Chin-Hsi
Highlights: Expert teachers had a closer relationship among the various practical knowledge. Novice teachers' mainly demonstrated knowledge of self, subject and learner. Colleague group may help knowledge connection, but couldn't replace expert teachers.